A power perturbation-based MTPA control with disturbance torque observer for IPMSM drive system. (June 2018) - Lin, Faa-Jeng; Chen, Shih-Gang; Liu, Ying-Tsen; Chen, Shih-Yao
A novel maximum torque per ampere (MTPA) method based on power perturbation for a field-oriented control (FOC) interior permanent magnet synchronous motor (IPMSM) drive system is proposed in this study. The proposed MTPA method is designed based on the power perturbation resulting from the signal injection in the current angle. Moreover, the influence of current and voltage harmonics to the MTPA control can be effectively eliminated. Furthermore, to enhance the robustness of the control system, a real-time design scheme for the integral–proportional (IP) speed controller using a recursive least square (RLS) estimator with disturbance torque feedforward control is developed. The disturbance torque is obtained from an improved disturbance torque observer with online parameters updated. Finally, some experimental results using an IPMSM drive system based on a low-price digital signal processor (DSP) are presented. From the experimental results, the proposed control approach can guarantee the control performance of a speed loop even under a cyclic fluctuating load.